2010
DOI: 10.1093/fampra/cmq072
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risk factors for chronic low back pain in primary care--a systematic review

Abstract: Few independent psychosocial risk factors have been demonstrated to exist. Randomized clinical trials aimed at modifying these factors have shown little impact on patient prognosis. Qualitative research might be valuable to explore further the field of LBP and to define new management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
191
2
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(222 citation statements)
references
References 74 publications
12
191
2
9
Order By: Relevance
“…10 Avoidance of activities because of fear of pain or injury is an approach to protecting the back that negatively influences outcome. 9 Our findings show that clinicians can contribute to avoidance beliefs directly by focusing upon what patients should not do and indirectly by providing management advice and pathoanatomic explanations, which are interpreted as meaning the spine is vulnerable and requires protection. Nearly all participants reported receiving pathoanatomic explanations for the cause of their back pain, despite guideline recommendations against doing so.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…10 Avoidance of activities because of fear of pain or injury is an approach to protecting the back that negatively influences outcome. 9 Our findings show that clinicians can contribute to avoidance beliefs directly by focusing upon what patients should not do and indirectly by providing management advice and pathoanatomic explanations, which are interpreted as meaning the spine is vulnerable and requires protection. Nearly all participants reported receiving pathoanatomic explanations for the cause of their back pain, despite guideline recommendations against doing so.…”
Section: Discussionmentioning
confidence: 75%
“…7,8 Depression, passive coping strategies, fear avoidance beliefs (the avoidance of movement or activity resulting from fear of pain or injury), and low expectations of recovery are independently associated with poor outcome. 9,10 A clinical guide to assessing psychosocial warning signs (yellow flags) developed in New Zealand has been adopted internationally. 11 Patients' beliefs need to be better understood to improve management of low back pain.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found depression to be associated with an increased risk of developing LBP (6)(7)(8), while other studies have failed to show a significant association (9)(10)(11). Previous reviews investigating the role of psychological variables in LBP have shown evidence of depression as a predictor of poor outcomes, such as chronicity, disability, and work absenteeism (12)(13)(14). However, these reviews did not specifically focus on premorbid depression as a risk factor for new cases of LBP.…”
Section: Introductionmentioning
confidence: 99%
“…These factors can be aggregated into a smaller number of categories [9] including biomechanical factors (regular lifting, exposure to vibration, physically demanding jobs, bending and twisting, pushing and pulling heavy loads, awkward posture) [2,[7][8][9][10][11][12][13][14][15][16][17][18][19][20], psychological/psychosocial factors (job satisfaction, local support in the workplace, depression, job control, stress) [2,7,9,16,[19][20][21][22][23][24][25] and individual risk factors (sedentary lifestyle, age, smoking, gender, obesity, poor general health, marital status, pregnancy) [2,7,9,12,13,20,21,23,[26][27][28][29][30][31]. Past studies have investigated many of these factors and their relationship to LBP.…”
Section: Introductionmentioning
confidence: 99%